Models for multi-state survival data : rates, risks, and pseudo-values - Andersen, Per Kragh; Ravn, Henrik. (Biostatistician) (Boca Raton : CRC Press, Taylor and Francis Group, 2024)
"Multi-state models provide a statistical framework for studying longitudinal data on subjects when focus is on the occurrence of events that the subjects may experience over time. They find application particularly in biostatistics, medicine, and public health. The book includes mathematical detail which can be skipped by readers more interested in the practical examples. It is aimed at biostatisticians and at readers with an interest in the topic having a more applied background, such as epidemiology. This book builds on several courses the authors have taught on the subject"--
Includes bibliographical references (pages 261-270) and index.
Keywords: Survival analysis (Biometry); Clinical trials -- Statistical methods; Statistics; Models for Multi State Survival Data